PRACTICES AND TRENDS IN VISUAL MERCHANDISING IN INDIAN RETAIL MALLS: A REVIEW (International Journal of Food and Nutritional Sciences, 2022)
Visual merchandising plays a crucial role in influencing consumer behavior and enhancing the overall shopping experience in retail environments. With the proliferation of retail malls across India, understanding the practices and trends in visual merchandising becomes imperative for retailers seeking to stay competitive in the market. This review paper synthesizes existing literature on visual merchandising practices and trends specifically within the context of Indian retail malls. It examines various elements of visual merchandising such as store layout, display techniques, signage, lighting, and sensory marketing strategies. Furthermore, it explores the impact of cultural factors, technological advancements, and consumer preferences on visual merchandising strategies employed by retailers in Indian retail malls. By providing a comprehensive overview of current practices and emerging trends, this paper offers insights for both academics and practitioners to optimize visual merchandising strategies in the Indian retail landscape.